The Design Concepts of "Shanashel", and its Effect on Functional and Environmental Performance - Niema, Saba Jabar (Iraqi Journal of Architecture and Planning, 2009)
The design concepts of uaditional architecture have had greet potentiality through time for all social and environmental needs of the place and its inhabitance. And the idea of analyzing their contents and meaning to understand their effects in architecture on it both sides (theory and practice), in order to adapt their beneficial parameters for modem architecture is so important for environmental design. This research concems with one of the design concepts of the traditional houses in the old fabric of the city which is the (Shanashel), and discuses their geometrical configuration, formal look, and material effect to show its functional and environmental performance (climate and acoustics). And has emphasized the later, as the facades acts as screens which attenuate sounds due to banier theory and have good influence on acoustical environment through diffusion and diffraction. In order to have some design parameters for architectural design and research process within the modern look.